Pemahaman Asbābun Nuzūl dan Signifikansinya dalam Ilmu Tafsir - Dendi Irwansa; Sutrisno Hadi; Muhammad Arpah; Pathur Rahman (Jurnal Teologi Islam, 2026)
ABSTRACT Asbāb al-Nuzūl is one of the branches of Qur’anic studies that examines the causes or events underlying the revelation of Qur’anic verses. This discipline holds a crucial position in efforts to understand the meaning of the verses comprehensively and contextually. This study aims to explore the definition, forms, and sources of asbāb al-nuzūl, as well as to analyze its role in the interpretation of the Qur’an. The method used is a qualitative approach through library research, which involves collecting and analyzing data from classical and contemporary tafsīr literature, such as the works of al-Wāhidī, al-Suyūṭī, Ibn Kathīr, and other modern mufassirīn. The results of the study indicate that asbāb al-nuzūl plays a highly significant role in understanding the context of revelation, thereby preventing textual and ahistorical misinterpretations. By understanding asbāb al-nuzūl, interpreters can grasp the social situations and conditions at the time of the revelation, as well as determine the scope of the legal rulings or moral messages contained in the verses more accurately. Moreover, asbāb al-nuzūl assists in distinguishing between general and specific verses and clarifies the relationship between the text and its context. Therefore, asbāb al-nuzūl is not merely a historical record of the revelation of verses but also serves as an important methodological tool in the science of tafsīr. This study emphasizes that understanding asbāb al-nuzūl is one of the key factors in interpreting the Qur’an correctly, contextually, and in accordance with the objectives of Shariah (maqāṣid al-sharī‘ah).